Negotiating Islamic Law through Custom: Resistance in Family Law Practices among the Anak Dalam Community in Jambi - Illy Yanti; Yuliatin Yuliatin; Siti Mahmudah; Mahluddin Mahluddin; Yuniar Galuh Larasati (Journal of Islamic Law)
This article explores how the Suku Anak Dalam (SAD) community resists the application of Islamic law in family matters, specifically in the determination of dower (mahr), the management of joint property, and the distribution of inheritance. While most SAD members have formally converted to Islam, their legal practices remain rooted in a matrilineal customary system passed down through generations. Challenging prevailing scholarly emphasis on integrative frameworks between Islamic law and local custom, this study demonstrates that, in the SAD context, resistance emerges when elements of Islamic jurisprudence (fiqh) clash with the community’s socio-cultural structure and shared values. Using a socio-legal approach and qualitative methods, the research draws on in-depth interviews with seven key informants, including a religious leader, the tumenggung (tribal chief), customary elder, community facilitator, subdistrict head, and SAD community members. The findings reveal a persistent orientation toward collective female authority: mahr is determined by the bride’s maternal kin group; joint property, upon divorce, is granted entirely to the wife; and inheritance follows a strictly matrilineal line. Rather than rejecting Islamic law on theological grounds, this resistance reflects a form of public reasoning grounded in ancestral consensus. The study highlights the importance of interpreting Islamic law through contextual, dialogical, and adaptive lenses—particularly within societies shaped by legal pluralism.